Pro-sustainability design in the training of women and the lack of dissemination of the fashion product in digital media (ModaPalavra e-periódico, 2023)
This study presents an educational strategy developed by NGO Trama Ética Institute during the fashion course “Mãos à Ecomoda”, held between October and December 2021 in the city of Florianópolis/SC. It aims to highlight the training of women focused on pro-sustainability design and how the educational process can be linked to the contribution of the digital environment of social networks. The theoretical framework used in the approach of the object included bibliographical research on the topics upcycling, circularity in the production and consumption chain, ethical fashion, sustainable fashion and digital media. Because it is an applied research, reports were used as support to describe the activities developed during the project, and content analysis as a resource to deal with the collected reports. The main results pointed to a good acceptance of the pro-sustainability theme in fashion among the participants of this course, as well as the relevance of investments in extension projects focused on the theme of sustainability, being a tool for reducing social and environmental impacts caused by the fashion sector. Finally, the final considerations reveal a distancing of the community observed in relation to digital technologies, signaling social and informational inequalities.
Keywords: Training of women; Design pro-sustainability; Digital media